PEMBERDAYAAN WARGA MASYARAKAT GENENGAN MELALUI PENYULUHAN DAN PELATIHAN MOKSIBASI UNTUK HIPERKOLESTEROL - Kurnia Eka Putri; Sri Yatmihatun (Rena Cipta Mandiri, 2025)
Background: A study conducted in Surakarta City revealed that 76% of individuals with hypertension also experienced hypercholesterolemia, and the risk of developing high cholesterol levels was 23% higher compared to those with normal cholesterol levels. In addition to causing hypertension, hypercholesterolemia can also lead to coronary heart disease (CHD). Moreover, the presence of high cholesterol in hypertensive patients increases the risk of developing CHD. Purpose and Benefits: This community service proposal aims to empower health cadres and the local community through education and training on moxibustion therapy for managing hypercholesterolemia. Methods: The activity will involve education and practical training for health cadres and residents of Genengan Village to prevent and manage cases of hypercholesterolemia. The program is scheduled to take place from July to November 2024. Results: The community will be able to apply moxibustion therapy to lower cholesterol levels and enhance their immune system.